Characterising health promotion in Aboriginal and Torres Strait Islander languages: A content analysis of COVID‐19 and maternal health resources. (31st March 2022) - Gaborit, Lorane; Robinson, Melanie; Sutherland, Stewart
Abstract: Issue addressed: Health promotion resources in Aboriginal and Torres Strait Islander (Indigenous) languages are being widely translated and disseminated at the community, health service and government level. In addition to outlining the relevant Australian policy context and evidence base, this study sought to describe the availability and characteristics of COVID‐19 and maternal health promotion resources incorporating Indigenous languages. Methods: Health promotion resources published online between June 2005 and June 2020 were identified by a desktop scan and screened against quality inclusion criteria. A content analysis by resource type, health topic, purpose, use of language and source was conducted. Results: A total of 215 resources was eligible for inclusion, incorporating 50 different Indigenous languages and representing a varied approach to language use and health promotion. Almost 7 times as many COVID‐19 resources were identified than maternal health materials. Conclusions: In contrast to maternal health, COVID‐19 has seen a sharp rise in the number of health promotion resources produced in language, especially in formats capable of streamlined replication in multiple languages. Strong use of narrative, storytelling and alternative primary aims such as language education suggests potential for greater collaboration between health promotion organisations and other community groups and services. Bilingual resources may have applications for communities where traditional language knowledge is being reawakened. So what?: Emerging capacity to efficiently produce health promotion resources in multiple Indigenous languages could be capitalised for health topics beyond COVID‐19. However, further research in determining best practice and user perspectives is essential in guiding the development of these resources.